2016
DOI: 10.1515/revneuro-2015-0018
|View full text |Cite
|
Sign up to set email alerts
|

The multifunctional lateral geniculate nucleus

Abstract: AbstractProviding the critical link between the retina and visual cortex, the well-studied lateral geniculate nucleus (LGN) has stood out as a structure in search of a function exceeding the mundane ‘relay’. For many mammals, it is structurally impressive: Exquisite lamination, sophisticated microcircuits, and blending of multiple inputs suggest some fundamental transform. This impression is bolstered by the fact that numerically, the retina accounts for a small fraction of its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 212 publications
(285 reference statements)
1
49
0
1
Order By: Relevance
“…Importantly, convergence differs among information streams in the cat, where TC Y-cells receive more RGC inputs (~10 inputs) than X-cells (Robson et al, 1993; Weyand 2016). In mice, functional distinctions between TC neurons types are still debated (Krahe et al, 2011; Denman and Contreras, 2016), and distinct convergence modes were not obvious in our analysis of >90 FFs (Fig 4H).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, convergence differs among information streams in the cat, where TC Y-cells receive more RGC inputs (~10 inputs) than X-cells (Robson et al, 1993; Weyand 2016). In mice, functional distinctions between TC neurons types are still debated (Krahe et al, 2011; Denman and Contreras, 2016), and distinct convergence modes were not obvious in our analysis of >90 FFs (Fig 4H).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating data from primates, cats, and mice have supported the view that thalamocortical relay (TC) neurons receive convergent inputs from one dominant RGC, with additional weaker RGC inputs evident in the cat (Cleland and Levick, 1971; Mastronarde, 1992; Usrey et al, 1999). In vivo recordings showed that one RGC input often dominates spiking of a TC neuron and connected RGC-TC neuron pairs exhibit very similar center-surround receptive fields in cats and primates (Weyand, 2016). In vitro slice recordings also showed ~1–3 RGCs innervate a TC neuron in mice (Chen and Regehr, 2000; Jaubert-Miazza et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Modulatory feedback from cortex, cholinergic inputs from a subset of brainstem nuclei, and inhibition from interneurons, endows the dLGN with the ability to shape visual information before transmitting it to higher cortical centers (Piscopo et al, 2013; Roth et al, 2016; Weyand, 2016; Rompani et al, 2017). For example, top-down feedback from corticothalamic inputs is thought to increase the selectivity of TC relay cells, sharpen TC relay cell receptive field properties, enhance synchronicity among TC relay cells, and influence the gain of retinogeniculate transmission (Sherman & Guillery, 2002; Briggs & Usrey, 2008; Weyand, 2016). In nocturnal rodents (and higher mammals) the manner in which retinal inputs innervate dLGN offers the possibility of modifying light-derived signals: feed forward inhibition of retinal inputs through local interneurons can either enhance temporal specificity of RG transmission or can enhance lateral inhibition (Martinez et al, 2014; Weyand, 2016), single retinal axons innervating multiple TC relay cells can amplify visual signals (Weyand, 2016), and the convergence of numerous retinal axons on single relay cell dendrites can produce TC receptive fields that are not present in retina (Hammer et al, 2015; Morgan et al, 2016; Weyand, 2016; Rompani et al, 2017).…”
Section: Diverse Connectivity Leads To Diverse Functions Of Retinorecmentioning
confidence: 99%
“…In vivo , the retinogeniculate synapse has been a prominent model system for the study of sub-cortical visual processing. Numerous studies have capitalized on the ease of manipulating visual stimulation, combined with the ability to simultaneously monitor the activity patterns of inputs and outputs of the thalamus to reliably demonstrate that the transfer of information from the retina to the visual cortex is the major function of the retinogeniculate synapse (Sherman, 2005; Usrey & Alitto, 2015; Weyand, 2016). …”
Section: More Than a Relaymentioning
confidence: 99%